2017
DOI: 10.3892/ijmm.2017.3205
|View full text |Cite
|
Sign up to set email alerts
|

Persistent STAT5-mediated ROS production and involvement of aberrant p53 apoptotic signaling in the resistance of chronic myeloid leukemia to imatinib

Abstract: The persistent activation of signal transducer and activator of transcription 5 (STAT5) may principally be attributed to breakpoint cluster region (BCR)-Abelson murine leukemia viral oncogene homolog 1 (ABL1), and have multi-faceted effects in the development of chronic myeloid leukemia (CML). The p53 protein network regulates important mechanisms in DNA damage repair, cell cycle regulation/checkpoints, and cell senescence and apoptosis, as demonstrated by its ability to positively regulate the expression of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Altered activation of STAT5A which affected by BCR-ABL tyrosine kinase can influence the CML development and progression [41]. Consistent with previously described [42], we found significantly increased expression level of STAT5 in CML cell lines and patients, especially in Imatinib-resistant patients and CML cell line. Besides, the new downstream axis of STAT5A was explored in the study.…”
supporting
confidence: 91%
“…Altered activation of STAT5A which affected by BCR-ABL tyrosine kinase can influence the CML development and progression [41]. Consistent with previously described [42], we found significantly increased expression level of STAT5 in CML cell lines and patients, especially in Imatinib-resistant patients and CML cell line. Besides, the new downstream axis of STAT5A was explored in the study.…”
supporting
confidence: 91%
“…Imatinib functions as a specific inhibitor of a number of tyrosine kinase enzymes, and it is used to treat Bcr/Abl‐positive CML and acute lymphocytic leukemia (Cheng et al, ). Flow cytometry results demonstrated that combining costunolide with imatinib inhibited K562 cell growth more than either compound alone; the combination of the two treatments dramatically suppressed growth and induced apoptosis in 34.51% ± 4.23% of the cells compared with 1.52% ± 0.51% in the control group, 19.58% ± 3.26% in the costunolide‐treated group, and 19.46% ± 4.08% in the imatinib‐treated group (IC 50 ; Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The p53 protein network regulates important mechanisms in DNA damage repair, cell cycle regulation/checkpoints, and cell senescence and apoptosis, as demonstrated by its ability to positively regulate the expression of various pro-apoptotic genes [ 47 ]. In addition, research shows that p53 can stably induce CML cell apoptosis [ 48 ]. Cyclin-dependent kinases (CDKS) are a family of serine/threonine kinases that have been firmly established as key regulators of transcription processes underlying coordinated cell cycle entry and sequential progression in nearly all types of proliferative cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%